Price Sensitivity Measurement: A Yield Management Approach - Okan Çolak; Levent Koşan (Istanbul Business Research (IBR), 2021)
The purpose of this paper is to investigate and identify the potential revenue losses, at price points determined by price sensitivity measurement, between actual revenue and potential revenue that can be gained, in terms of yield management. A case study was carried out in a 5 star hotel business in Aydın, Turkey. In the study, a questionnaire was conducted to determine price resistance levels, price threshold limits, price sensitivity levels and price perceptions based on the room quality perceptions of the tourists visiting the hotel business. Also, an interview was performed with the accounting manager and the front office manager about the room prices determined. Hotel businesses can determine the optimal price by depending on the quality and value perception of the customers; thus they can use their limited capacity more efficiently so that they can maximize yield. This study showed that the hotel business lost room revenue at all points calculated. The hotel business suffered a potential loss of 35-40% because of the high occupancy rate in July and August. The hotel industry could have room sales revenues much more than the actual room sales revenues, especially if the agency commission expenses can be reduced.
Keywords: 650; Yield management; Price Sensitivity Measurement; Willingness-to-pay; All Inclusive System; Hotel Management